Microplastic: pollution issue and seafood security - Khusnul Yaqin (Sekolah Tinggi Ilmu Pertanian Wuna, 2021)
At the first time, plastic materials were produced to facilitate various activities of human life. Plastic materials that are flexible and durable have been used by humans to meet various needs to support their daily activities. Starting from human activities from waking up to going back to sleep, nowadays it cannot be separated from the use of plastic materials. This then makes humans